Determination of the fundamental absorption and optical bandgap of dielectric thin films from single optical transmittance measurements - Tejada A. (2019)
In this work, we propose a method to retrieve the thickness and optical constants of dielectric thin films from single optical transmittance measurements. The method is based on the envelope method and requires a simple dispersion model for the real part of the refractive index with few fitting parameters, while the absorption coefficient can be determined without the aid of a dispersion model. The wavelength-dependent optical constants can be obtained even from spectra that exhibit few interference fringes. We have tested the method with simulated and real transmittance data from thin films in the spectral range covering the fundamental absorption. In order to assess the method’s reliability to retrieve the optical constants and optical bandgap, a comparison is performed with the method by Chambouleyron, known as the Pointwise Unconstrained Minimization Approach, and a fit using the Cody–Lorentz dispersion model. We evaluate the methods’ capability to retrieve the fundamental absorption and optical bandgap, and their compromise with film thickness accuracy. Finally, the methods are tested and contrasted using optical transmittance of three different semiconductor material thin films. © 2019 Optical Society of America